The Effect of Job Satisfaction and Work Discipline on Employee Performance at BPRS Bhakti Sumekar Sumenep: Pengaruh Kepuasan Kerja dan Disiplin Kerja Terhadap Prestasi Kerja Karyawan pada BPRS Bhakti Sumekar Sumenep - Putri, Andik Bone; Maftuhah, Rifa'atul; Rafsanjani, Haqiqi (Universitas Muhammadiyah Sidoarjo, 2023)
The bank itself is a financial institution that plays an important role in the economy of a country. The more developed the banking industry, the better the country's economic growth. Bank as a financial institution whose function is to collect and distribute funds to the public in order to increase equity, economic growth and stability. Thus, banks are able to collect and distribute public funds effectively and efficiently towards improving people's living standards. The main objectives of the researchers are (1) to find out whether there is a significant influence on job satisfaction on employee work, (2) to find out whether there is a significant influence on work discipline on employee work, and (3) to find out whether there is a significant effect simultaneously between the two variables namely job satisfaction and work discipline on the work performance of BPRS Bhakti Sumekar Sumenep employees. This research method was conducted using a quantitative approach. The population in this study were all employees of BPRS Bhakti Sumekar Sumenep, totaling 51 employees. In this study the sample technique used was saturated sampling where all members of the population were selected as samples. Data collection in this study was a questionnaire or questionnaire, then testing in analyzing information through classical assumption tests, multiple linear regression tests, and hypothesis testing using SPSS 26 software. positive and significant to employee performance (Y) tcount of 2.974 > ttable 2.00 with a significant value level of 0.238 less than 0.05. While Work Discipline (X2) by t test has a positive and significant effect on Employee Performance (Y) tcount of 4.156 > ttable 2.00 with a significant value level of 0.000 less than 0.05. Simultaneously, having an Fcount value of 30,731 while Ftable is 2.79. Because Fcount > Ftable (30,731 > 2.79) and a significance of 0.000 <0.05. And the magnitude of the job satisfaction variable (X1) and work discipline variable (X2) can be seen from the assessment of other variables outside the model. This value indicates that variations in employee work variables are influenced by job satisfaction (X1) and work discipline (X2).